find g(-1) if g(x)=x^3+3x^2+3x+1
![find g1 if gxx33x23x1 class=](https://us-static.z-dn.net/files/dd4/02cdb3a7fe6eb4eabe2e610e0c0c49f7.jpg)
Option (c) [tex]0.[/tex]
Step-by-step explanation:
Put x = -1 Then,
[tex]g( - 1) = {( - 1)}^{3} + 3 {( - 1)}^{2} + 3( - 1) + 1[/tex]
[tex]g( - 1) = - 1 + 3 - 3 + 1[/tex]
Here, -1 , +1 gets cancelled and +3 , -3 gets cancelled. Hence,
[tex]g( - 1) = 0.[/tex]
Answer:
g-1 =0
Step-by-step explanation:
x+1 is factor then f(−1)=0
Replace x in p(x) by −1 we get
f(x)=x
3
+3x
2
+3x+1
or,f(−1)=(−1)
3
+3(−1)
2
+3(−1)+1
or,f(−1)=−1+3−3+1
or,f(−1)=0